The Relationship Between Perceived Staffing Adequacy and Burnout Levels Among Nurses in the Inpatient Units of RSPAD Gatot Soebroto Hospital - Aisyah Rania Hasriadi; Didin Syaefudin; Ita Ita (Journal of Innovative and Creativity, 2026)
ABSTRACT Burnout among nurses is a persistent occupational problem that may compromise nurses’ well-being and the quality of patient care. One contributing factor is perceived staffing adequacy, particularly in inpatient settings where workload intensity is high. Insufficient staffing may increase emotional exhaustion and work-related stress among nurses. Purpose: This study aimed to examine the relationship between perceived staffing adequacy and burnout levels among nurses in the inpatient units of RSPAD Gatot Soebroto Hospital. Methods: A quantitative correlational study with a cross-sectional design was conducted involving 57 inpatient nurses selected using purposive sampling. Perceived staffing adequacy was measured using the Nurse Perceived Adequacy of Staffing Scale (NPASS), while burnout levels were assessed using the Maslach Burnout Inventory–Human Services Survey (MBI-HSS). Data were analyzed using the Chi-square test with a significance level of 0.05. Results: The findings showed that most nurses perceived staffing adequacy as moderate (39%), while 31% perceived it as adequate and 30% as inadequate. Burnout levels were categorized as low (33%), moderate (37%), and high (30%). Statistical analysis revealed a significant relationship between perceived staffing adequacy and burnout levels among nurses (p = 0.017). Nurses who perceived staffing as inadequate tended to experience higher levels of burnout. Conclusion: There is a significant relationship between perceived staffing adequacy and burnout among inpatient nurses. Improving staffing allocation and addressing nurses’ perceptions of workload adequacy may help reduce burnout and promote a healthier work environment in hospital inpatient units.